2002
DOI: 10.1074/jbc.m110901200
|View full text |Cite
|
Sign up to set email alerts
|

The Forkhead Transcription Factor AFX Activates Apoptosis by Induction of the BCL-6 Transcriptional Repressor

Abstract: The activation of the AKT/protein kinase B kinases by mutation of the PTEN lipid phosphatase results in enhanced survival of a diversity of tumors. This resistance to apoptosis is partly accomplished by the inhibition of genetic programs induced by a subfamily of forkhead transcription factors including AFX. Here we describe an AFX-regulated pathway that appears to account for at least part of this apoptotic regulatory system. Cells induced to synthesize an active form of AFX die by activating the apoptotic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
154
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(161 citation statements)
references
References 45 publications
6
154
0
1
Order By: Relevance
“…It is possible that some of these genes are targets of transcription factors such as the FoxO family of Forkhead factors that are known to be negatively regulated by PI 3-kinase, which is activated downstream of the EGF receptor. Indeed, two of the down-regulated EGF receptor-dependent genes, bcl-6 and IGFBP1, are known targets of FoxO transcription factors (Tang et al, 1999(Tang et al, , 2002. In addition, three of the remaining genes contain FoxO binding sites in their promoter regions as determined by sequence analysis (A.Schulze and J.Downward, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that some of these genes are targets of transcription factors such as the FoxO family of Forkhead factors that are known to be negatively regulated by PI 3-kinase, which is activated downstream of the EGF receptor. Indeed, two of the down-regulated EGF receptor-dependent genes, bcl-6 and IGFBP1, are known targets of FoxO transcription factors (Tang et al, 1999(Tang et al, , 2002. In addition, three of the remaining genes contain FoxO binding sites in their promoter regions as determined by sequence analysis (A.Schulze and J.Downward, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, SIRT1 attenuates p53-dependent apoptosis specifically because it does not affect p53-independent Fas-mediated apoptosis. 35 In addition to p53, four members of the FOXO subgroup (FOXO1/ FKHR, FOXO3/FKHRL1, FOXO4/AFX and FOXO6) have been identified in mammals, and their participation in the regulation of apoptosis, 36,37 cell-cycle arrest, DNA repair and oxidative stress resistance 38 has been demonstrated. SIRT1 may deacetylate p300 and repress p300-mediated activation of FOXO3.…”
Section: Resveratrol Restored Icp and Increased The Ratio Of Icp/mapmentioning
confidence: 99%
“…Moreover, in response to DNA damage, FoxO3a has also been shown to activate the expression of the growth arrest and DNA damage response gene GADD45a to mediate G2/M cell cycle arrest and trigger DNA repair (Tran et al, 2002). Recently, one of the pro-survival Bcl-2 family members, Bcl-XL, which is an important downstream target of FoxO (Tang et al, 2002), has been shown to colocalize and bind to CDC2 during G2/M phase progression and its overexpression stabilizes a G2/M arrest senescence programme in surviving cells after DNA damage (Schmitt et al, 2007). Thus, these data would suggest that FoxO can directly regulate a series of cell cycle proteins, and depending on stimuli, control both G1/S and G2/M phase progression.…”
Section: Foxo and The G1/s Phase Transitionmentioning
confidence: 99%
“…Besides the conventional antiapoptotic function, Bcl-XL has recently been shown to stabilize G2/M cell cycle arrest through direct interaction with CDC2 (Schmitt et al, 2007). Analogous to cyclin D2, FoxO-induced Bcl-6 activation represses Bcl-XL at the transcriptional level (Tang et al, 2002). The activation of FoxO1 by CPT-11 is impeded by CDK2 which phosphorylates FoxO1, causing the nuclear exclusion of the transcription factor .…”
Section: Foxo-cell Cycle and Apoptosismentioning
confidence: 99%